Pengaruh Citra Brand, Kualitas Program dan Personal Selling Terhadap Pengambilan Keputusan untuk Membeli Program dari Mentari Group - Maman, Maman; Handoko, Yunus; Kusdyah Rachmawati, Ike (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
The purpose of this study is to examine and analyze the influence of brand image, program quality, and the personal selling capabilities of the sales and marketing team on the decision-making process of schools in purchasing programs from Mentari Group as a medium to support learning activities. The data collection method used in this study was a questionnaire, with a total sample of 153 respondents. The research findings indicate that the variables of Brand Image, Program Quality, and Personal Selling simultaneously have a significant effect on Decision-Making. Furthermore, on a partial basis, this study demonstrates that the Brand Image variable (X1) has a significance value of 0.006 < 0.05, leading to the conclusion that the Brand Image variable (X1) significantly influences Decision-Making (Y). The Program Quality variable (X2) has a significance value of 0.108 > 0.05, indicating that the Program Quality variable (X2) does not influence Decision-Making (Y). The Personal Selling variable (X3) has a significance value of 0.000 < 0.05, leading to the conclusion that the Personal Selling variable (X3) significantly influences Decision-Making (Y).